2014
DOI: 10.1007/s10802-014-9858-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parents’ Literacy Skills and Children’s Preliteracy Skills on the Risk of Dyslexia

Abstract: The combination of investigating child and family characteristics sheds light on the constellation of risk factors that can ultimately lead to dyslexia. This family-risk study examines plausible preschool risk factors and their specificity. Participants (N = 196, 42 % girls) included familial risk (FR) children with and without dyslexia in Grade 3 and controls. First, we found impairments in phonological awareness, rapid naming, and letter knowledge in FR kindergartners with later dyslexia, and mild phonologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
67
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 50 publications
12
67
4
1
Order By: Relevance
“…These three factors may explain most of the contrasting results concerning attention. However, the results pertaining to math are not as clear-cut: in contrast with the results of this research, some studies have found a connection between RAN and math even after controlling for reading fluency van Bergen et al, 2014). One explanation that may partly resolve this discrepancy derives from the composition of the samples studied.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…These three factors may explain most of the contrasting results concerning attention. However, the results pertaining to math are not as clear-cut: in contrast with the results of this research, some studies have found a connection between RAN and math even after controlling for reading fluency van Bergen et al, 2014). One explanation that may partly resolve this discrepancy derives from the composition of the samples studied.…”
contrasting
confidence: 99%
“…double-deficit was associated with the existence of RD, and not with comorbidity per se, as while the prevalence of RDs was elevated in the double-deficit group, no difference emerged between the DDH groups in the prevalence of math disability or attention deficit. In sum, the results from Studies I and II were in line with those of previous studies where RAN has been linked with reading but not specifically to performance in math or attention Georgiou, Tziraki et al, 2013;.The results of this research are in conflict with previous findings in which RAN has been associated with math performance (Ackerman et al, 2001;Murphy, Mazzocco, Hanich, & Early, 2007;van Bergen et al, 2014; or with attention deficits (Arnett et al, 2012;Tannock et al, 2000;. There are several possible explanations for this.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…This finding was expected because rapid naming has been shown to be a strong predictor of reading speed measures (e.g., Puolakanaho et al, 2007;van Bergen et al, 2014a). The skills of the late-emerging group seemed to be sufficient for the early grades, but not for reaching the typical level of fluency in reading in later grades.…”
Section: Discussionmentioning
confidence: 94%
“…Family risk has predicted children's reading development over and above children's skills in the key cognitive precursors, such as phonological awareness, rapid naming, and letter knowledge (Puolakanaho et al, 2007;Torppa, Eklund, van Bergen, & Lyytinen, 2011). Furthermore, studies predicting children's skills with parent's skills have suggested that specific parental skills may be informative in assessing children's liability for dyslexia beyond their own cognitive development (Torppa et al, 2011;van Bergen et al, 2014a).…”
Section: Late-emerging and Resolving Dyslexia: A Follow-up Study Frommentioning
confidence: 99%